Data assimilation in the laboratory using a rotating annulus experiment - Young, R; Read, P (2013)
The thermally driven rotating annulus is a laboratory experiment important for the study of the dynamics of planetary atmospheres under controllable and reproducible conditions. We use the analysis correction method to assimilate laboratory data into an annulus model. We analyze the 2S and 3AV regular flow regimes between rotation rates of 0.75 and 0.875 rad s and the 3SV chaotic flow regime between rotation rates of 2.2 and 3.1 rad s. Our assimilated observations are irregularly distributed, which is more meteorologically realistic than gridded observations as used in recent applications of data assimilation to laboratory measurements. We demonstrate that data assimilation can be used successfully and accurately in this context. We examine a number of specific assimilation scenarios: a wave-number transition between two regimes, information propagation from data-rich to data-poor regions, the response of the assimilation to a strong disturbance to the flow, and a vortex-shedding instability phenomenon at high rotation rate. At the highest rotation rates we calculated the barotropic E-vectors using unobserved variables such as temperature and the vertical structure of the velocity field that are only available via the assimilation. These showed that the mean flow is weakened by the action of eddies, going some way towards explaining why vortices are shed at the very highest rotation rates but not at lower rotation. Rossby-wave stability theory suggests that the underlying instability leading to vortex shedding may be baroclinic in character. © 2012 Royal Meteorological Society.